ANALYSIS OF THE APPLICATION OF THE UTAUT2 MODEL ON THE USE OF E-COMMERCE FEATURES IN THE BSI MOBILE BANKING APPLICATION - wulan Dari Bancin, Intan; Nurbaiti, Nurbaiti; Ahmadi Bi Rahmani, Nur (JURNAL EKBIS, 2025)
The rapid development of today’s era means that every person, organization or company must also have ideas and creativity to continue to keep the company or business attractive and left behind. Therefore, this research aims to find out how to apply the UTAUT2 model to the use of E-commerce features in the BSI mobile banking application. This research uses descriptive quantitative analysis research methods which aim to test theories, build facts, show relationships between variables, provide statistical descriptions, estimate and predict results. The data in this research uses secondary data, namely data from questionnaire results. The data analysis technique in this research is quantitative descriptive, starting with the t test, then continuing with the F test. The results of this research are that performance expectations, business expectations, habits, social influence, facilitating conditions, hedonic motivation, price value, interest in use have a significant effect on e-commerce features. The value of Fcount > Ttable (295.705 > 1.98), as well as the significance value (0.000 < 0.05). In the research that has been conducted, it Is proven that the variables of facilitating conditions, hedonic motivation, and price value influence the intention to use e-commerce features, and the variables of habit and intention to use influence the behavior of using e-commerce.